2004
DOI: 10.4049/jimmunol.173.8.5008
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Glucocorticoid-Induced TNFR Family-Related Receptor on Effector T Cells by its Ligand Mediates Resistance to Suppression by CD4+CD25+ T Cells

Abstract: Nonactivated CD4+CD25+ regulatory T cells constitutively express glucocorticoid-induced TNFR family-related receptor (GITR), a TNFR family member whose engagement was presumed to abrogate regulatory T cell-mediated suppression. Using GITR−/− mice, we report that GITR engagement on CD25−, not CD25+ T cells abrogates T cell-mediated suppression. Mouse APCs constitutively express GITR ligand (GITR-L), which is down-regulated following TLR signaling in vivo. Although GITR−/−CD25− T cells were capable of mounting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
467
5
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(499 citation statements)
references
References 41 publications
24
467
5
3
Order By: Relevance
“…Thus, this CD4 + T cell population was associated with suppressive activity during acute FV infection. In addition, it has been reported that the treatment of FV or LP-BM5 retrovirus (which induces mouse AIDS) infected mice with an antibody against GITR, which has been suggested to either block the suppressive function of Treg cells [20], or to make CD8 + T cells refractory to Treg suppression [30], can overcome CD8 + T cell dysfunction and virusinduced immunosuppression [31,32]. Taken together, these findings indicate that CD4 + CD25 -GITR + CD103 + T cells might be an important population of induced Treg in chronic retroviral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this CD4 + T cell population was associated with suppressive activity during acute FV infection. In addition, it has been reported that the treatment of FV or LP-BM5 retrovirus (which induces mouse AIDS) infected mice with an antibody against GITR, which has been suggested to either block the suppressive function of Treg cells [20], or to make CD8 + T cells refractory to Treg suppression [30], can overcome CD8 + T cell dysfunction and virusinduced immunosuppression [31,32]. Taken together, these findings indicate that CD4 + CD25 -GITR + CD103 + T cells might be an important population of induced Treg in chronic retroviral infection.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Importantly, engagement of GITR using anti-GITR mAb (DTA-1) caused CD25 -responder T cells to escape suppression by CD25 + CD4 + T R cells as well [34] (Fig. 4B) and abrogated accumulation of ICER/CREM in T R assays to levels comparable to Fab-anti-CTLA-4 (UC-10) mAb treatment (Fig.…”
Section: Abrogation Of T R -Mediated Suppression By Ctla-4 Blockade Pmentioning
confidence: 93%
“…A possibility is that IL-21 selectively induces on CD4 ϩ T cells specific molecules that may, in turn, antagonize the activity of CD4 ϩ CD25 ϩ T cells. A potential candidate could be the glucocorticoid-induced TNFR family-related receptor ligand, as it was recently shown that such a protein can be also expressed by T cells and provide signals that make CD4 ϩ CD25 Ϫ T cells resistant to CD25 ϩ T cell-mediated suppression (22). Studies are now in progress to address this issue.…”
Section: Discussionmentioning
confidence: 99%